2019
DOI: 10.1302/1863-2548.13.180160
|View full text |Cite
|
Sign up to set email alerts
|

Autism and toe-walking: Are they related? Trends and treatment patterns between 2005 and 2016

Abstract: Purpose This study quantified toe-walking trends and treatment decisions in patients with autism spectrum disorder (ASD) in the United States between 2005 and 2016 using a large national private-payer database. Methods A retrospective database review was performed on paediatric patients with ASD, and for International Classification of Diseases-9/10 diagnosis codes for toe-walking. Patients were filtered based on treatment type by Current Procedural Terminology (CPT) code. Continued toe-walking rates were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 27 publications
(49 reference statements)
1
25
0
1
Order By: Relevance
“… Bone changes, including reduced bone mineral density and bone cortical thickness in boys, as well as increased risks of hip, spine, and forearm fractures [ 101 , 102 ]. Abnormal posturing and walking on tiptoes [ 103 ], likely indicating idiopathic intracranial hypertension, which can be induced by vitamin A intoxication [ 104 ]. This can cause foot drop, which forces the individual to walk on tiptoes.…”
Section: Vitamin a And Immune Functionmentioning
confidence: 99%
See 2 more Smart Citations
“… Bone changes, including reduced bone mineral density and bone cortical thickness in boys, as well as increased risks of hip, spine, and forearm fractures [ 101 , 102 ]. Abnormal posturing and walking on tiptoes [ 103 ], likely indicating idiopathic intracranial hypertension, which can be induced by vitamin A intoxication [ 104 ]. This can cause foot drop, which forces the individual to walk on tiptoes.…”
Section: Vitamin a And Immune Functionmentioning
confidence: 99%
“…Abnormal posturing and walking on tiptoes [ 103 ], likely indicating idiopathic intracranial hypertension, which can be induced by vitamin A intoxication [ 104 ]. This can cause foot drop, which forces the individual to walk on tiptoes.…”
Section: Vitamin a And Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leyden et al. (2019) found that nearly 75% of individuals with ASD who have surgery to reduce ITW begin toe walking again within 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Furrer and Deonna analyzed “persistent toe-walking” in 28 children, and failure to explain this abnormal gait pattern with known disease processes was diagnosed as “habitual toe-walking.” 8 Today, the literature most commonly uses the term “idiopathic toe walking,” with continued questions about its etiology, natural history, and appropriate treatment 9 . Some studies report a higher incidence of ITW in children with autism spectrum disorder, and thus far, the pathophysiology of this association is unexplained 6,10 .…”
mentioning
confidence: 98%